A formative approach to employee retention using structural equation modelling. (2017) - Deepa, M.; Resmi, A.T.
The study analyses the antecedents of employee retention using a structural equation modelling. Healthcare professionals are critical in the provision of the health sector, particularly nurses who are very valuable to the organisations since they are the ones who provide firsthand service to the patients, it is important to ensure that skilled nurses are retained and the voluntary turnover among them is managed properly. There were 189 sets of questionnaire randomly distributed to the healthcare professionals in hospitals. The questionnaire consists of 100 items with fixed alternative construct questions. The respondents were asked to rate the questions in five point Likert scaling method which allows respondents to understand the questions clearly. The study found that 67% of employee retention is resultant of job involvement, organisational citizenship behaviour, people management practices, organisation loyalty, and employee empowerment. This study provides ample evidences from literature about the predictors of employee retention and provides an empirical base to induce employee retention in hospitals.